2018
DOI: 10.3390/su10010125
|View full text |Cite
|
Sign up to set email alerts
|

Two Scenarios for Landfills Design in Special Conditions Using the HELP Model: A Case Study in Babylon Governorate, Iraq

Abstract: Abstract:The sound design of landfills is essential in order to protect human health and the environment (air, water, and soil). The study area, Babylon Governorate, is situated in the middle of Iraq, and is distinguished by a hot climate and shallow groundwater. The governorate did not have landfill sites that meet international criteria; in addition, the groundwater depth in Babylon Governorate is commonly shallow. Previously, the most important criteria for the study area and GIS software were used to selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The area of each zone is divided into number of cells to receive the waste quantity (for one month) based on the supposed lifespan for one zone ( Fig. 4) [16]. Eq.…”
Section: Landfills Site Layoutmentioning
confidence: 99%
See 1 more Smart Citation
“…The area of each zone is divided into number of cells to receive the waste quantity (for one month) based on the supposed lifespan for one zone ( Fig. 4) [16]. Eq.…”
Section: Landfills Site Layoutmentioning
confidence: 99%
“…In addition, the amount of runoff and actual evapotranspiration that result from rainfall was estimated when the suggested layers were used for the final cover system of landfill [12][13][14]. In the literature reviews, several previous studies used the different versions of the HELP model to estimate the leachate within the landfill sites (e.g., [4,[15][16][17][18][19]).…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation plays an important role [Dregulo 2019], which increases the humidity of sewage precipitation. In this case, unstable compounds dissociate to form the cation-anion complexes capable of a long migration path [Chabuk et al 2018; Abd El-Salam and I Abu-Zuid 2015; Naveen et al 2018; Luczkiewicz 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Sumathi et al [25] proposed GIS-based procedures that combined the use of GIS with a multicriteria analysis, Zamorano et al [26] applied the procedure to a case study in Southern Spain and Simsek et al [10] explicitly considered NIMBY syndrome constraints. Other case studies can be found in [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%